Archaea express circular isoforms of IS200/IS605-associated ωRNAs - Picinato, Beatriz A.; Franceschini-Santos, Vinícius H.; Zaramela, Lívia S.; Vêncio, Ricardo Z. N.; Koide, Tie (Frontiers in Microbiology, 2025)
Circular RNAs (circRNAs) are RNA molecules with 5′ and 3′ ends covalently ligated. Their functions range from acting as genetic regulators to producing proteins, and they are often expressed in a tissue and condition-specific manner. Next-generation sequencing with prior RNA treatment with the RNase R exonuclease (circRNA-Seq) has been used to identify circRNAs in many organisms, especially in model eukaryotes. However, we know little about circRNAs in prokaryotes: they have not been consistently reported in bacteria and, to date, only a few circRNA-Seq studies have been done in archaea. We have developed a prokaryotic-specific computational pipeline, MonArch, that explores RNA-Seq reads for circRNA signatures. We annotated circRNAs in newly generated Halobacterium salinarum circRNA-Seq data and reanalyzed over 20 archaeal public RNA-Seq datasets with this tool. H. salinarum has 49 high-confidence circRNAs, with some validated by RT-PCR. We detected known circular ribosomal RNA and transfer RNA processing intermediates and novel circRNAs associated with ωRNAs (obligate mobile element–guided activity - OMEGA) and IS200/IS605 transposases. The ωRNAs circular isoforms have a growth-dependent expression pattern, distinct from the total ωRNAs levels. This is one of the few examples of prokaryotic circRNAs with a conditional expression pattern. In all the other public archaea circRNA-Seq data (Haloferax volcanii, Saccharolobus solfataricus, Sulfolobus acidocaldarius, and Pyrococcus abyssi), we found circRNAs associated with the same classes of transcripts as for H. salinarum, including circRNAs in IS200/IS605 transposases in the two Sulfolobales species. We broadened our search for circRNAs in representatives of major archaeal groups, and found that circRNAs associated with the rRNA and tRNA are widespread, indicating conserved processing of these transcripts. Circular ωRNAs are also present in other haloarchaeal species. Together, our results show that circRNAs appear to be conserved and abundant among archaea, maybe more than previously appreciated. The circular ωRNAs are present in different distant archaeal species, and are a new piece in the IS200/IS605 system.